Concentrations and Size Distributions of Bacteria-Containing Particles over Oceans from China to the Arctic Ocean - Ming Li; Xiawei Yu; Hui Kang; Zhouqing Xie; Pengfei Zhang (Atmosphere, 2017)
During the third China Arctic Research Expedition (July–September 2008), size-resolved measurements of bacteria-containing particles (BCPs) in the marine boundary layer (MBL) air were conducted during a cruise through the East China Sea, the Yellow Sea, the Japan Sea, the Okhotsk Sea, the Bering Sea, the Chukchi Sea, and the Arctic Ocean. The concentrations of total airborne BCPs (TBCPs), non-salt tolerant airborne BCPs (NSBCPs), and salt tolerant airborne BCPs (SBCPs) varied from 29 to 955 CFU m−3 (CFU = Colony Forming Unit), 16 to 919 CFU m−3, and 4 to 276 CFU m−3, with an average value of 275, 182, and 92 CFU m−3, respectively. Although the SBCP concentrations were less than the NSBCP concentrations when averaged over all measurements, there are several cases where the reverse is true (e.g., in the high Arctic Ocean). During the cruise, the TBCP sizes were dominated by the diameter >4.7 μm fraction (accounted for 46.3% on average), while the fine fraction (diameter <2.1 μm) accounted for 27.8%. For NSBCPs and SBCPs, the coarse fraction also was the dominant fraction over most regions. The influence of local meteorological conditions on the abundance, size distributions, and species of airborne bacteria is discussed. Notably, in the atmosphere over the Arctic Ocean the abundance of airborne bacteria was apparently related to the distribution of sea ice. As cultivation based methodologies may underestimate the environmental bacterial communities, it is expected that the abundance of bacteria in the ambient air would be higher than that observed in this study. In order to distinguish different species of bacteria, molecular biological techniques (e.g., 16S rDNA analysis) are required for identification in future investigations.